Trends in Hospital Admissions for Chronic Obstructive Pulmonary Diseases After Comprehensive Tobacco Control Policies in Beijing, China. Issue 12 (3rd June 2022) - Wu, Yiqun; Wang, Zijing; Zheng, Yunting; Wang, Mengying; Wang, Siyue; Wang, Jiating; Wu, Junhui; Wu, Tao; Chang, Chun; Hu, Yonghua
Abstract: Introduction: Only a few studies have examined the effectiveness of tobacco control policies on respiratory conditions, and the results were less consistent. The 2015 Beijing tobacco control policy package incorporating all six components of MPOWER has been implemented since Jun 2015. The present study aimed to evaluate the impact of a comprehensive tobacco control policy package on hospital admissions for chronic obstructive pulmonary disease (COPD) in Beijing, China. Aims and Methods: An interrupted time-series study was conducted based on the hospital admission information for about 18 million residents, who were covered by the Beijing Medical Claim Data for Employees from January 2013 to June 2017. The average percentage change of COPD hospital admission rates and reductions in hospital admission numbers were estimated by segmented Poisson regression models. Results: There were 54 040 COPD hospital admissions with a crude rate of 67.2 per 100 000 residents during the observational period. After the implementation of the policy package, the hospital admission rates of COPD were reduced by −14.7% (95%CI: −17.8%, −11.5%) immediately. The secular trend was slowed down by −3.0% (95% CI: −5.6%, −0.4%) annually. A total of 5 581 reductions in COPD hospital admissions were estimated during the 25 months post-law period, accounting for 17.5% (95% CI: 12.5%, 22.5%) of overall COPD hospital admissions. More reductions were shown in males and those aged over 65 years old. Conclusions: The results indicated significant protections against hospitalization of COPD after the 2015 Beijing comprehensive tobacco control policy package. The results provide support for public health benefits for respiratory conditions from WHO-recommended tobacco control measures. Implications: Only a few studies have examined the effectiveness of tobacco control policies on respiratory conditions, and the results were less consistent. Based on medical records for about 18 million residents, this study showed an association between comprehensive tobacco control policies and significant reductions of hospital admissions for chronic obstructive pulmonary disease. The results provide support for public health benefits for respiratory conditions from WHO-recommended tobacco control measures.